1999
DOI: 10.1159/000008105
|View full text |Cite
|
Sign up to set email alerts
|

Prolongation of the Frequency-Corrected QT Dispersion following Cerebral Strokes with Involvement of the Insula of Reil

Abstract: Prolonged QT dispersion is a risk factor for cardiac arrhythmias and sudden death in patients with cardiac and peripheral artery diseases, but there is no study about prolonged QT dispersion in patients with ischaemic strokes. The insular cortex may play an important role in the genesis of cardiac arrhythmias and sudden death. In our study with 40 patients suffering from unilateral hemispheric ischaemic stroke, the QT dispersion was analysed and correlated to the location of the cerebral lesion. We found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 9 publications
0
28
0
3
Order By: Relevance
“…From our experiments, ventricular ectopy was a most frequently observed malignant arrhythmia. Previous studies have shown the presence of either inverted T waves or severe QTc prolongation had a sensitivity of 100% and a specificity of 81% for predicting left ventricular dysfunction [26,27]. The QT intervals were significantly longer in cerebral ischemic rats (Figure 2B), which significantly indicated that cardiac conduction had slowed [28] and affected ventricular repolarization of cardiac myocytes in cerebral ischemic rats.…”
Section: Discussionmentioning
confidence: 72%
“…From our experiments, ventricular ectopy was a most frequently observed malignant arrhythmia. Previous studies have shown the presence of either inverted T waves or severe QTc prolongation had a sensitivity of 100% and a specificity of 81% for predicting left ventricular dysfunction [26,27]. The QT intervals were significantly longer in cerebral ischemic rats (Figure 2B), which significantly indicated that cardiac conduction had slowed [28] and affected ventricular repolarization of cardiac myocytes in cerebral ischemic rats.…”
Section: Discussionmentioning
confidence: 72%
“…As an example, cerebrovascular disease involving the insular cortex leads to significantly increased QT D [10, 11], perhaps because of increased sympathetic activity that is observed (particularly after involvement of right insular cortex [12]). In fact, QT D measurements were recommended in cases of acute stroke [11].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding repolarization inhomogeneity, QT dispersion is increased after acute stroke compared to age-matched hospitalized controls, both groups without history or clinical evidence of cardiac disease [15]. Since this was noted only within 24 hours of stroke onset, it strengthens the association and interestingly, was noted specifically with insular infarcts [16]. Further insular association arises from the linkage between right insular stroke and AV block, QTc prolongation, T wave inversion and ventricular ectopy, (these not observed with strokes in other locations) and with increased mortality at 3 months [17,18].…”
Section: Strokementioning
confidence: 75%